Oxygen generating electrode

By optimizing the composition and stability coefficient of ceramic materials, the problem of insufficient phase stability of ceramic materials under alkaline water electrolysis conditions is solved, low-cost and low overpotential hydrogen production is achieved, reducing hydrogen production costs and increasing electrodes Durability.

CN119137312AActive Publication Date: 2024-12-13OÜ STARGATE HYDROGEN SOLUTIONS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380037847.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-18
Filing Date
2023-04-17
Publication Date
2024-12-13
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The existing ceramic materials have insufficient phase stability under alkaline water electrolysis conditions, resulting in high overpotential of oxygen-generating electrodes and high cost of traditional precious metal materials, making it difficult to achieve low-cost and efficient hydrogen production.

Method used

The composition formula [(Ax)A'(1-x)]yBzB'(1-z)O3-δ adopts ceramic material, where A and A' are rare earth or alkaline earth metals, and B and B' are transition metals, by stabilization Coefficient (SF) optimizes the phase stability and electrochemical activity of ceramic materials to ensure that the overpotential is maintained under high temperature and high alkali conditions.

Benefits of technology

The phase stability and low overpotential of the electrode under industrial-related conditions are achieved, which reduces the cost of hydrogen production, avoids the use of precious metals, and improves the durability and stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137312A_ABST
    Figure CN119137312A_ABST
Patent Text Reader

Abstract

An electrode for an oxygen evolution reaction suitable for water electrolysis under alkaline conditions, comprising a ceramic material having a stability coefficient (SF) between 1.67 < = SF < = 2.8, calculated by formula (II) wherein ro represents the ion radius of the oxide ion (O2-), rB, av represents the weighted average ion radius of the transition metal, nA, nB, av represents the weighted average ion radius of the transition metal, nA represents the ion radius of the oxide ion (O2-), nA represents the ion radius of the oxide ion (O2-), nA represents the ion radius of the oxide ion (O2-), and nA represents the ion radius of the oxide ion (O2-). Av represents the weighted average oxidation state of the rare earth metal or the alkaline earth metal, and rA and av represent the weighted average ion radius of the rare earth metal or the alkaline earth metal. The invention further relates to an alkaline electrolysis stack comprising at least one such electrode, and to a method for water electrolysis using the alkaline electrolysis stack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode for electrolysis, in particular to an electrode suitable for oxygen generation in water electrolysis under alkaline conditions, the electrode having a low overpotential in the oxygen evolution reaction. The present invention also relates to an alkaline electrolysis stack comprising at least one such electrode, and a method for water electrolysis using the alkaline electrolysis stack under alkaline conditions. Background Art

[0002] In alkaline water electrolysis, water is electrochemically converted into hydrogen and oxygen under alkaline conditions: H2O = H2 + 0.5O2. The electrolytic cell contains two electrodes: an anode and a cathode. During operation, an electric potential is applied between the two electrodes, causing an electrolytic current to flow in the electrolytic cell. During operation, hydrogen is generated at the cathode by the hydrogen evolution reaction (HER): 2H2O + 2e - =H2+2OH - , and oxygen is generated at the anode by the oxygen evolution reaction (OER): 2OH - =0.5O2+H2O+2e - The alkaline electrolytic cell also includes an electrolyte, which includes a liquid alkaline medium, such as an aqueous solution of hydroxide and / or carbonate. The electrolytic cell also includes a porous diaphragm and / or an ion exchange membrane capable of conducting hydroxide ions.

[0003] In alkaline water electrolysis, it is ideally desirable to minimize both the input cost and the energy consumption of the electrolytic cell. All else being equal, the lower the input cost and energy consumption, the lower the production cost of the hydrogen produced by electrolysis. The input cost of the electrolytic cell is minimized when low-cost materials are used in the electrolytic cell and these electrolytic cells are produced by low-cost production methods. For a fixed operating current or current density, the energy consumption of the electrolytic cell is also minimized when the required applied potential (voltage) is minimized.

[0004] The required applied potential is the sum of multiple potentials, including: 1) the theoretical potential required for the electrochemical reaction; 2) the potential due to the porous diaphragm and / or ion exchange membrane; 3) the overpotential caused by the anode; 4) the overpotential caused by the cathode; 5) the potential related to the distance between the anode and the cathode in the electrolytic cell. Here, the term "overpotential" refers to the difference between the theoretical potential and the actual potential applied to each electrode, and includes, for example, the potential caused by the formation of bubbles. It is well known to those skilled in the art that the overpotential of the anode (OER electrode) is generally higher than the overpotential of the cathode (HER electrode). Therefore, it is very critical to develop improved oxygen generation electrodes. In particular, these electrodes should be made of low-cost materials and produced using low-cost manufacturing methods, while exhibiting lower overpotentials than existing electrodes in terms of OER.

[0005] In industrial alkaline electrolyzers, OER electrodes are typically made of nickel or precious metals. Nickel-based electrodes are relatively low cost, but their overpotential is high, resulting in high energy consumption of the electrolyzer and thus high cost of hydrogen production. In contrast, electrodes based on precious metals or their compounds (such as IrO2, RuO2, Pt) have lower overpotentials, but the input costs are very high, resulting in high cost of hydrogen production. A third class of alkaline electrolysis OER electrode materials has been discovered and demonstrated to exhibit low overpotentials while maintaining low costs. Specifically, ceramic materials with specific crystal structures, such as perovskite structures, have proven to be particularly attractive alternatives to nickel and precious metals for making OER electrodes.

[0006] The formula of this type of ceramic material is described in WO 2013 / 012965 A1, which was applied by the Massachusetts Institute of Technology and published on January 24, 2013. The article discloses an OER catalyst, which is expressed as A x A' 1-x B y B' 1-y O 3±δ , wherein A and A' are each a rare earth metal or an alkaline earth metal, x ranges from 0 to 1, B and B' are each a transition metal, y ranges from 0 to 1, and δ ranges from 0 to 1. Example materials described in the referenced applications include LaCrO3, LaMnO3, LaFeO3, LaCoO3, LaNiO3, LaNi 0.5 Mn 0.5 O3、LaCu 0.5 Mn 0.5 O3, La 0.5 Ca 0.5 MnO 3-δ ,La 0.5 Ca 0.5 FeO 3-δ,La 0.75 Ca 0.25 FeO 3-δ ,La 0.5 Ca 0.5 CoO 3-δ 、LaMnO 3-δ and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ The number of materials that can be described by the above expression is virtually infinite, although some materials are described by their composition as A x A' 1- x B y B' 1-y O 3±δ , but are not as suitable as other materials for use in alkaline electrolytic cells. x A' 1-x B y B' 1-y O 3±δ It is claimed, however, that when the occupancies of the σ-bonding orbitals of B, B' with eg symmetry or each element in B and B' are within a specific range, it leads to high activity in OER. More specifically, Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ It was found to have particularly high OER activity: an OER current of 100 mA / cm at an electrode overpotential of 0.4 V in 0.1 M KOH 2 In contrast, the OER currents of IrO2 and RuO2 electrodes under the same conditions were 18 mA / cm 2 and 5mA / cm 2 .

[0007] The method proposed in WO 2013 / 012965 A1 mainly addresses the problem of insufficient stability of the claimed materials under the conditions used in industrial alkaline water electrolysis cells. The authors of WO 2013 / 012965 A1 then show that the most electrocatalytically active of the materials mentioned is Ba which has lost its crystalline structure when subjected to OER in 0.1 M KOH solution. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ and SrCo 0.8 Fe 0.2 O 3-δ,, while some other materials, especially LaCoO3, did not lose their crystal structure (cited from the journal: J.Phys.Chem.C, 117 (2013) 8628 author, Risch et al.). In general, the loss of crystal structure or the selective leaching of elements in the material means that the OER activity is reduced (i.e., the overpotential is increased).

[0008] US 2016 / 0289850A1, applied by DE NORA TECH INC of the United States and published on October 6, 2016, describes the use conditions of an industrial alkaline water electrolysis cell: 5-30 wt% alkaline electrolyte KOH or NaOH (e.g., 25% by weight KOH) is preheated to 80°C. Therefore, compared with a 1M KOH solution at room temperature, achieving material stability under industrial conditions is more challenging. At high temperatures (e.g., 80°C), the use of concentrated alkaline solutions (e.g., 25% by weight KOH) can further reduce the applied potential required for the industrial alkaline water electrolysis cell. The use of high temperatures and high alkali concentrations not only has a positive effect on the anode potential, but also improves the potential caused by the porous diaphragm and / or ion exchange membrane (increased conductivity of the diaphragm and / or membrane), the overpotential of the cathode, and the potential associated with the distance between the anode and the cathode (increased conductivity of the electrolyte, resulting in a lower ohmic drop). Therefore, as described in WO 2013 / 012965A1, although using a lower concentration alkaline solution at a lower temperature may be more beneficial to the anode from the perspective of stability, the improvement in anode performance usually cannot compensate for the performance degradation of other components of the electrolytic cell caused by lower temperature and lower alkaline concentration.

[0009] Therefore, there is still a need to find new ceramic materials that are low-cost, can produce low OER overpotentials, and can remain stable under industrially relevant conditions (i.e., high temperature and concentrated alkaline solutions). Summary of the invention

[0010] The inventors hope to produce low-cost hydrogen by alkaline water electrolysis. The inventors found that in the prior art, ceramic-based anodes still have defects. More specifically, the anode initially exhibits the lowest OER overpotential, such as Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ Anodes with low OER overpotentials rapidly deactivate under industrially relevant electrolysis conditions due to insufficient phase stability. On the other hand, anodes that do not deactivate under industrially relevant electrolysis conditions usually exhibit extremely high OER overpotentials. Currently, the search for anode materials that do not deactivate but exhibit low OER overpotentials relies mainly on intuition and trial and error.

[0011] The inventors have discovered that a parameter, called the "stability factor", abbreviated as SF, can successfully predict the phase stability of ceramic materials suitable for alkaline electrolytic cell anodes. More specifically, based on the SF value, the stability of certain ceramic materials in strong alkaline solutions and their OER activity (activity is inversely proportional to the overpotential) can be estimated. Therefore, the following types of materials can be divided: a) highly active but phase-unstable materials, b) phase-stable but inactive materials, and c) simultaneously active and phase-stable materials. Highly active but phase-unstable materials have relatively high SF values, while phase-stable but inactive materials have relatively low SF values. Materials with intermediate SF values ​​exhibit both sufficient electrochemical activity (i.e., low OER electrode overpotential) and sufficient phase stability.

[0012] According to one aspect of the present invention, an electrode for conducting water electrolysis oxygen reaction under alkaline conditions is provided, wherein the electrode comprises a ceramic material [(A x )A' (1-x) ] y B z B' (1-z) O 3-δ , wherein each A and A' is independently a rare earth metal or an alkaline earth metal, x ranges from 0 to 1, y is the A site occupancy ranging from 0.5 to 0.99, each B and B' is independently a transition metal, z ranges from 0 to 1, O is oxygen, δ is the oxygen non-stoichiometric ratio ranging from -1 to 1, and the SF of the ceramic material is greater than or equal to 1.67 and less than or equal to 2.8.

[0013] In the context of the present invention, "stability factor" or "SF" refers to a parameter defined as:

[0014]

[0015] Among them, r O Oxygen ions (O 2 -) ionic radius, r B,av is the weighted average ionic radius of B and B', n A,Av is the weighted average oxidation state of A and A', and r A,av is the weighted average ionic radius of A and A'.

[0016] The terms "phase stability" and "phase stable" refer to the property of a material to retain its crystalline phase when exposed to industrially relevant alkaline water electrolysis conditions. One method of assessing the phase stability of a material, or whether a material is phase stable, is to obtain X-ray diffraction patterns of the material before and after exposure to industrially relevant alkaline water electrolysis conditions. If there is no significant difference in the corresponding X-ray diffraction patterns, then phase stability is confirmed, i.e., no phase change has occurred in the bulk phase of the material. In the context of the present invention, "industrially relevant alkaline water electrolysis conditions" refers to exposure to an aqueous solution of KOH with a weight percentage of more than 20% at a temperature between 75-85 degrees Celsius, regardless of whether an electrolysis current is applied. In order to verify phase stability, the exposure time to the above conditions should be at least 24 hours, preferably at least 100 hours. Of course, there are other alternative methods for determining phase stability, but it should be noted that in the context of the present invention, surface-sensitive methods such as X-ray photoelectron spectroscopy or low-energy ion scattering are not suitable for determining phase stability because these methods cannot detect the bulk phase of the material.

[0017] In the formula of the present invention, "y" represents "A-site occupancy", which refers to the number of A-site cations relative to the number of B-site cations in the ceramic material. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (Can also be written as [Ba 0.5 Sr 0.5 ] 1.0 Co 0.8 Fe 0.2 O 3-δ ), y = 1.0. 0.95 CoO3 (also known as [La 1.0 ] 0.95 CoO3), y = 0.95. Note that when estimating the A-site occupancy, the B-site occupancy is considered equal to 1. For example, to calculate LaCo 1.05 O 3.16 The A-site occupancy of the material is expressed so that the subscript of the B-site cation (i.e., Co) is equal to 1, which gives La 0.95 CoO3, therefore y=0.95.

[0018] The terms “A site” and “B site” refer to sites of different energies in the crystal lattice of a ceramic material. It is important to note that although the formula [(A x )A' (1-x) ] y B z B' (1-z) O 3-δUsually refers to materials with a perovskite structure (ABO3) or a double perovskite structure (A2B2O5), but in the context of the present invention, the terms "A site" and "B site" are used more broadly and have nothing to do with the crystal structure of the ceramic material.

[0019] In the formula of the present invention, "δ" represents "oxygen non-stoichiometric ratio", which refers to the number of oxygen vacancies relative to B-site cations in the ceramic material. For example, for La 0.90 Ni 0.6 Fe 0.4 O 2.85 (Can also be written as La 0.90 Ni 0.6 Fe 0.4 O 3-0.15 ), δ = 0.15. In oxygen-excess compounds, δ is negative: for example, in La 0.3 Sr 0.7 TiO 3.15 (Can also be written as La 0.3 Sr 0.7 TiO 3+0.15 ), δ = -0.15. Note that under the premise of δ' = 1-2δ, any double perovskite A2B2O 5+δ , which can be expressed as ABO 3-δ The oxygen non-stoichiometric ratio depends on factors such as temperature, oxygen partial pressure and applied voltage.

[0020] As defined in RD Shannon, Acta Crystallogr. A, 32 (1976) 751-767, "ionic radius" refers to the Shannon ionic radius. For example, the oxygen anion O 2- When the coordination number is 2, the ionic radius is In the context of the present invention, the "weighted average ionic radius of A and A'" refers to the ionic radius that satisfies the formula [(A x )A' (1-x) ] y B z B' (1-z) O 3-δ The weighted average of the cation ionic radius of A and A' in the ceramic material, where the weight of the ionic radius of A is x and the weight of the ionic radius of A' is (1-x), and then the weighted average of the radius is multiplied by the A site occupancy y, and the formula is as follows:

[0021]

[0022] "r A ” refers to the ionic radius of A, “r A' " refers to the ionic radius of A', and the formula is as follows:

[0023] r B,Av = z·r B +(1-z)·r B′

[0024] The “weighted average oxidation state” is the average oxidation state of the x )A' (1-x) ] y B z B' (1-z) O 3-δ The weighted average of the oxidation states of cations A and A' in the ceramic material, where the weight of the oxidation state of A is x and the weight of the oxidation state of A' is (1-x), and then the weighted average of the oxidation states is multiplied by the A site occupancy y, and the formula is as follows:

[0025]

[0026] where n A is the oxidation state of A, n A' is the oxidation state of A'.

[0027] "Alkaline electrolysis stack" means a device comprising a plurality of alkaline electrolysis cells electrically connected together. The greater the number of cells in the stack, the more hydrogen and oxygen can be produced per unit time. Likewise, the greater the surface area (footprint) of each cell in the stack, the more hydrogen and oxygen can be produced. The electrodes of the electrolysis cells in the electrolysis stack are separated by porous separators (such as Zirfon) and / or ion exchange membranes capable of conducting hydroxide ions.

[0028] The above-mentioned embodiments of the present invention have several important advantages over the prior art. First, the electrode of the present invention has sufficient phase stability, which means that the electrode does not need to be frequently replaced during operation. Secondly, the electrode of the present invention has sufficient activity to enable it to achieve low overpotential and high efficiency, thereby reducing the cost of hydrogen production. Third, the electrode of the present invention does not contain precious metals such as iridium, platinum and ruthenium, thereby solving the problem of difficulty in obtaining electrode materials and significantly reducing the cost of electrode raw materials. Fourth, the electrode of the present invention has a lower overpotential in the oxygen evolution reaction than traditional nickel-based electrodes. Since electricity cost is the main factor determining the cost of producing hydrogen by electrolysis, the electrode of the present invention makes the production cost (operating cost) of hydrogen lower than that of traditional nickel-based electrodes.

[0029] EP3587622 A1, which was applied for by ASAHI KASEI KABUSHIKI KAISHA Co., Ltd. of Japan and published on January 1, 2020, describes an anode for water electrolysis, comprising a porous substrate and a metal oxide layer, the surface of the metal oxide layer contains at least one metal oxide with a perovskite structure, and the crystal component content of the perovskite structure metal oxide in the metal oxide layer is more than 90% but not more than 100%. EP 3587622 A1 also describes an anode, wherein the composition of the perovskite structure metal oxide can be expressed as A x A' (1-x) Ni y B' (1-y) O 3-z , wherein A and A' are alkaline earth metals or rare earth elements, B' is Cr, Mn, Fe, Co or Cu, x satisfies 0≤x≤1, y satisfies 0≤y≤1, and z satisfies 0≤z≤1. EP3587622A1 records that after 100 hours, or at 6kA / m 2 Overvoltage value under working condition, and confirm Ba 0.5 Sr 0.5 Co 0.8 FeO3 performs worse than LaNiO3 (probably due to poor phase stability). 0.5 Sr 0.5 Co 0.8 The SF value of FeO3 is 3.91, while that of LaNiO3 is 1.62. This indicates that Ba 0.5 Sr 0.5 Co 0.8 FeO3 has insufficient long-term stability under industrially relevant conditions, while LaNiO3 has too low oxygen evolution reaction (OER) activity, and its associated overpotential can be further reduced by increasing the A-site occupancy (0.5≤y≤0.99). In addition, the method of coating the perovskite on the surface of the nickel substrate is labor-intensive, requiring 13 coating and drying cycles followed by calcination cycles.

[0030] Ma et al. published a series of perovskite oxides in Journal of Alloy and Compounds, 854 (2021) 157154: La 0.95 FeO3、La 0.95 Fe 0.9 Co 0.1 O3, La 0.95 Fe 0.8 Co 0.2 O3, La 0.95 Fe 0.7 Co 0.3 O3 and La 0.95 Fe0.6 Co 0.4 O3. Among these five materials, Ma et al. did not further explain the La 0.95 FeO3 and La 0.95 Fe 0.6 Co 0.4 O3, focusing on the remaining three materials: La 0.95 Fe 0.9 Co 0.1 O3, La 0.95 Fe 0.8 Co 0.2 O3, La 0.95 Fe 0.7 Co 0.3 O3. The authors then subjected the three materials to a reduction treatment to induce the precipitation of Co or Co / Fe nanoparticles and then evaluated the OER performance of these materials. Importantly, during the reduction process, the composition of the original materials inevitably changes. For example, La 0.95 Fe 0.9 Co 0.1 O3 turns into LaFe 0.9 Co 0.1 O3 and Fe0.9Co0.1 (per mole La 0.95 Fe 0.9 Co 0.1 0.95 mol LaFe in O3 0.9 Co 0.1 O3 and 0.05 mol Fe0.9Co0.1). In all cases, the resulting material is no longer A-site deficient. LaFe 0.9 Co 0.1 O3, La 0.95 Fe 0.8 Co 0.2 O3 and La 0.95 Fe 0.7 Co 0.3 The stability coefficients of O3 are calculated to be 1.65, 1.65 and 1.66 respectively. The present invention is different from the document in that the material of the present invention does not cause the A-site ion deficiency or loss due to the reduction reaction.

[0031] Poznyak et al. disclosed a series of perovskite materials in Journal of Solid State Electrochemistry 12 (2008) 15-30: La 0.3 Sr 0.7 CoO 2.924 ,La 0.3 Sr 0.7 Co 0.8 Al 0.2 O 2.85 , (La0.3 Sr 0.7 ) 0.97 CoO 2.896 ,La 0.5 Sr 0.5 CoO3、La 0.55 Sr 0.45 CoO3、La 0.65 Sr 0.35 CoO3、La 0.7 Sr 0.3 CoO3、La2NiO 4.15 、La2Ni 0.9 Co 0.1 O 4.169 、La2Ni 0.8 Cu 0.2 O 4.124 Although some of these materials have a perovskite structure, one material has an A-site occupancy below 1, and some have a SF below 2.8, so no material in the literature satisfies all three conditions at the same time. Therefore, the present invention can be distinguished from the prior art.

[0032] According to one aspect of the invention, the electrode further comprises a second material, which is metallic nickel, a metal alloy of nickel and iron, or a hydroxide of nickel and iron. One advantage of combining a ceramic material with a second material rather than with a conventional electrode material is that the second material can provide partial electrochemical activity for the combined electrode. This is particularly important when the electrode is partially contaminated with impurities: if the electrode is made of a variety of materials, these materials have different affinities for different impurities, i.e., they are affected to different degrees by the adsorption of impurities. Therefore, electrodes comprising a variety of materials are generally more stable and durable than electrodes comprising only a single material. Please note that the second material can be composed before or after exposure under operating conditions. For example, it is known that iron impurities in the electrolyte may be deposited onto the electrode during operation.

[0033] EP3444383B1, which was applied for by DE NORA PERMELEC LTD of Japan and published on February 20, 2019, describes an anode for alkaline water electrolysis, comprising a conductive substrate composed of at least nickel or a nickel-based alloy, and an electrode catalyst layer formed on the surface of the conductive substrate, wherein the catalyst components constituting the electrode catalyst layer include: a first catalyst, whose components include: a nickel-cobalt spinel oxide with a structural formula of NiCo2O4, or a nickel-cobalt spinel oxide with a structural formula of XNiaCo 1- aLanthanide metal-nickel-cobalt perovskite oxides of O3 (where X represents at least one metal selected from lanthanide elements such as lanthanum, cerium, and praseodymium, and 0 < a < 1); and a second catalyst, the composition of which contains at least one iridium oxide and ruthenium oxide, where the amount of the second catalyst composition (calculated based on the amount of the metal component) is at least 0.2 g / m 2 . The perovskite materials described in EP 3444383 B1 generally exhibit very low SF values. For example, for all LaNiaCo 1-a O3 compositions, SF < 1.67: For example, LaNi 0.1 Co 0.9 O3 (SF = 1.66), LaNi 0.5 Co 0.5 O3 (SF = 1.64), LaNi 0.9 Co 0.1 O3 (SF = 1.63). In other words, the materials selected here are not ideal for OER: they are "too stable", and more active materials can be obtained by adjusting the A-site occupancy rate in the range of 0.5 to 0.99. In addition, the electrodes described in EP 3444383 B1 still contain a large amount of iridium and ruthenium oxides to achieve the required activity level. Due to the very limited content of these elements in the earth's crust, resulting in high costs, the use of iridium and ruthenium has problems.

[0034] According to an embodiment of the present invention, the ceramic material is uniformly dispersed on the surface of the second material. "X is uniformly dispersed on the surface of Y" means that on the premise that the inspection area is large enough, no matter which part of Y is inspected, the concentration of X particles on the surface of Y is the same. For example, "X" refers to the ceramic material and "Y" refers to the second material. In the context of the present invention, if the inspection area contains at least 500 X particles identified by an electron microscope, the inspection area is considered large enough. The advantage of dispersing the ceramic material on the surface of the second material is to obtain an electrode with uniform electrochemical activity. In addition, since the electrochemical reaction on the surface of the electrode material is related to a significant reaction enthalpy, the uniform dispersion of the ceramic material helps to avoid "hot spots" (local temperature gradients) in the electrode, which may damage the electrode structure or the separation membrane.

[0035] According to one aspect of the invention, particles of a ceramic material are fixed and partially coated by a second material. In the context of the present invention, "X is fixed" means that the particles of X cannot break away and move during operation of the electrolytic cell. In addition, "X is partially coated by Y" means that the contact between the particles of X and Y comes from multiple sides (partial coating) rather than all sides (complete coating). The advantage of this aspect is that the ceramic material is firmly locked during operation, thereby avoiding, for example, ceramic particles falling to the bottom due to gravity causing uneven electrode activity or mechanical problems. Partial coating is a particularly effective method for dispersing a ceramic material on the surface of a second material because it ensures that the ceramic material is firmly attached to the surface of the second material while still being exposed to the electrolyte, thereby maintaining electrochemical activity.

[0036] According to one aspect of the present invention, A is an element in the following element list: La (lanthanum), Ce (cerium), Gd (gadolinium), Pr (europium), Ba (barium); A' is an element in the following element list: Sr (strontium), Ca (calcium), Ba (barium), Ce (cerium); B or B' is an element in the following element list: Mn (manganese), Ni (nickel), Fe (iron), Co (cobalt), Ti (titanium), Cr (chromium). The advantage of selecting La, Ce, Gd, Pr or Ba as A is that they have a suitable cation size (La) in the perovskite lattice. 3+ 、Ce 3+ , Gd 3+ , Pr 3+ and Ba 2+ ), and the availability (price) of these elements. For example, from the perspective of ionic radius, Dy 3+ and Eu 3+ Also suitable, but not widely used due to their high prices. The advantage of choosing Sr, Ca, Ba or Ce as A' is that these elements can generally improve the electrical conductivity and oxygen vacancy concentration of the ceramic material. There are two advantages to choosing Mn, Ni, Fe, Co, Ti, Cr as B or B': First, the use of transition metals improves the electronic conductivity of the material because these metals have a variety of possible oxidation states, enabling, for example, polaron hopping conduction mechanisms. Second, due to the lower cost of Mn, Ni, Fe, Co, Ti or Cr compared to Ru or Ir, using Mn, Ni, Fe, Co, Ti or Cr as B or B' is better than using metals such as Ru or Ir as B or B'.

[0037] According to one embodiment of the present invention, the A-site occupancy, denoted as y, is in the range of 0.6 to 0.98, preferably in the range of 0.75 to 0.98. An A-site occupancy below unity (e.g., 0.9) is advantageous because it allows the A-site cations to be more tightly bound to the crystal structure. However, when the A-site occupancy is too low (e.g., below 0.6), some of the B-site cations may no longer be embedded in the structure of the ceramic material, resulting in some of the B cations forming a secondary oxide phase. The A-site occupancy has optimal results within a certain range, such as between 0.6 and 0.98, preferably between 0.75 and 0.98.

[0038] According to one embodiment of the present invention, the average particle size of the ceramic material is between 10nm and 300nm, preferably between 20nm and 200nm. Generally, the electrochemical and catalytic activities of the material increase with the increase of the surface area of ​​the material. Therefore, it is desirable to increase the surface area of ​​the ceramic material as much as possible, that is, to reduce the average particle size of the material. However, once the particle size is too small, for example, below 20nm, the properties of the material begin to change because more material atoms now occupy the edges and corners of the particles. This phenomenon not only affects the electrochemical activity of the material, but also affects the stability of the material, usually resulting in a decrease in stability. Therefore, the average particle size of the ceramic material should be within an optimal range, for example, between 10nm and 300nm or 20nm and 200nm.

[0039] According to one aspect of the invention, the ceramic material has a perovskite crystal structure. The perovskite structure is advantageous because it is an extremely versatile material that is generally more stable than the corresponding Ruddlesden-Popper phase (e.g., less sensitive to A-site cation leaching). Perovskites are generally more electrochemically active than the corresponding spinel phases.

[0040] According to one embodiment of the present invention, when the oxygen evolution reaction is carried out using a rotating disk electrode in 20% to 35% KOH at a temperature of 75 to 85 degrees Celsius at a rotation speed of 1500 rpm, at a current density of 1 mA / cm 2 The electrode of the present invention is optimized for industrial alkaline electrolysis conditions, that is, the weight percentage of KOH is 20% to 35% and the temperature is in the range of 75°C to 85°C. The overpotential of the electrode in the oxygen evolution reaction is minimized, and the overpotential of the electrode is reduced to 1 mA / cm 2The overpotential should be less than or equal to 400 mV to achieve performance at least comparable to that of state-of-the-art iridium-based electrodes. In a typical spinning disk electrode experiment, the ceramic material is deposited onto the electrode surface (e.g., a glassy carbon electrode) and immersed in a KOH solution. The electrode performance (overvoltage at different current densities) can be evaluated over a range of electrode rotation speeds to investigate the effects of kinetic and mass transport limitations. Ohmic losses can be corrected by additional electrochemical impedance spectroscopy measurements.

[0041] According to one embodiment of the present invention, the ceramic material has a phase stability of 100 hours in 6M KOH at 80 degrees Celsius. The general life of an alkaline electrolytic cell is about 10 years, and all materials used in such electrolytic cells must be able to withstand the operating conditions during the entire electrolytic cell life. However, in order to screen materials for alkaline electrolytic cells, exposure to 6M KOH at 80°C for 100 hours is generally sufficient to evaluate the phase stability of the material. After being exposed to 6M KOH at 80°C for 100 hours, materials that fail to maintain phase stability are not suitable for use as electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the relationship between the stability and activity of ceramic materials and the stability coefficient. DETAILED DESCRIPTION

[0043] Attached Figure 1 a shows the qualitative relationship (expressed in arbitrary units) between the phase stability (stability (au)) represented by the ordinate on the left and the stability factor (SF) represented by the abscissa. Specifically, when the SF value is low, the formula [(Ax)A'( 1-x )] y B z B' (1-z) O 3-δ The phase stability of ceramic materials with increased SF increases, i.e. they are less susceptible to decomposition and phase changes under electrolysis conditions. At higher SF values, the phase stability of such materials decreases, and when SF>2.8, these materials are no longer phase stable under industrially relevant electrolysis conditions. Therefore, materials with SF>2.8 are not particularly suitable for use as oxygen electrodes in alkaline electrolysis cells.

[0044] In addition, Figure 1 a also shows the qualitative relationship (expressed in arbitrary units) between the electrochemical activity (activity (au)) on the right vertical axis and the stability factor (SF) on the horizontal axis. Specifically, when the SF value is high, the formula [(Ax)A'( 1-x )] y B z B' (1-z) O 3-δThe electrochemical activity of ceramic materials increases, i.e. the overpotential for the oxygen evolution reaction (OER) decreases when these materials are exposed to electrolysis conditions. The activity of such materials decreases at lower SF values ​​and, at SF < 1.67, these materials are no longer sufficiently active under industrially relevant electrolysis conditions. Therefore, materials with SF < 1.67 are not particularly suitable for use as oxygen electrodes in alkaline electrolysis cells.

[0045] Attached Figure 1 b shows the qualitative relationship (expressed in arbitrary units) between the parameter "stability multiplied by activity" represented by the ordinate and the stability factor (SF) represented by the abscissa. When 1.67≤SF≤2.8, the best performance material is obtained, that is, it has both high stability and high activity.

[0046] Best Mode for Carrying Out the Invention

[0047] This method is described in more detail in the following non-limiting example.

[0048] Example 1 (Comparison example)

[0049] Table 1 lists the relevant material properties and SF values ​​of some ceramic materials in the BaSrCo ferrite family. 2+ At a coordination number of 12, the Shannon ionic radius is And Sr 2+ At a coordination number of 9, the ionic radius is From this we get Co 3+ At a coordination number of 6, the ion radius of the Sanon is Fe 3+ At a coordination number of 6, the ionic radius is The corresponding r is provided in Table 1 B,av Regardless of the Co:Fe ratio, y = 1 (Ba 0.5 Sr 0.5 ) 1.0 Co z Fe 1-z O 2.5 The SF value of the material remains almost unchanged. For example, Ba with y=1 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 2.5 The SF value is 3.50, Ba 0.5 Sr 0.5 Co 0.2 Fe 0.8 The SF value of O3 is 3.49. In other words, no matter in (Ba 0.5 Sr 0.5 ) 1.0 Coz Fe 1-z The material is predicted to be phase-instable under conditions relevant to industrial alkaline electrolysis by selecting the Co:Fe ratio in O3. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ It is unstable in 0.1 M KOH.

[0050] The materials in Table 1 can be synthesized using (but not limited to) solid state synthesis, coprecipitation, hydrothermal synthesis, sol-gel synthesis, chemical vapor deposition, spray pyrolysis, atmospheric plasma deposition, etc., by mixing the metal precursors in the desired proportions and optionally treating the resulting mixture to form the correct crystalline phase. The same method can also be used to synthesize the materials described in the following examples.

[0051] Table 1

[0052]

[0053] Example 2 (Comparison example)

[0054] Table 2 lists some relevant material properties and SF values ​​of ceramic materials of the barium strontium cobalt ferrite family. 0.5 Sr 0.5 ) y Co 0.8 Fe 0.2 O 3-δ The A-site occupancy y of the material changes systematically in the range of 0.7≤y≤1. As the y value decreases, the SF value increases, that is, the phase stability of the material decreases. 0.5 Sr 0.5 ) y Co 0.8 Fe 0.2 O 3-δ For any chosen value of y, the material is predicted to be phase-instable under conditions relevant to industrial alkaline electrolysis.

[0055] Table 2

[0056]

[0057] Example 3 (Comparative Example)

[0058] Table 3 lists some relevant material properties and SF values ​​of ceramic materials of the barium strontium cobalt ferrite family. x Sr 1-x ) 1.0 Co 0.8 Fe 0.2 O2.5 The Ba:Sr ratio x of the material is systematically varied within the range of 0.1≤x≤0.9. x Sr 1-x ) 1.0 Co 0.8 Fe 0.2 O 2.5 No matter how large the x value is chosen, it is predicted that the material will not be phase stable under the conditions relevant to industrial alkaline electrolysis.

[0059] Table 3

[0060]

[0061] Example 4 (Comparative Example)

[0062] Table 4 lists some (A 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 The relevant material properties and SF values ​​of O3 family ceramic materials. In Table 4, by 2+ 、Ce 3+ , Gd 3+ , Pr 3+ and La 3+ Choose different A, an element in the A-position cation, (A 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 3-δ A systematic change in Ba 2+ At a coordination number of 12, the ion radius of the Sanon is And Sr 2+ At a coordination number of 9, the ionic radius is Get 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.5 of La 3+ At a coordination number of 12, the ion radius of the Sanon is (12 coordination), we get (La 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.75 of Ce 3+ (12-coordinated), Pr 3+(9-coordinated) and Gd 3+ The radii of the (8-coordinated) ions are and The obtained material (Gd 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.75 、(Pr 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.75 , (La 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.75 and (Ce 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.75 The SF values ​​of (Ba 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 2.5 SF = 3.5. Therefore, it is expected that in material (A 0.5 Sr 0.5 ) 1.0 Co 0.8 Fe 0.2 O 3-δ Among them, the materials selected as Ce, Gd, Pr and La are more phase-stable than the materials selected as Ba, but these materials are not stable enough and are not suitable for use in industrial alkaline electrolytic cells.

[0063] Table 4

[0064]

[0065]

[0066] Example 5

[0067] Table 5 lists some relevant material properties and SF values ​​of ceramic materials of the GdSrCoFerrite family. x Sr 1-x ) 0.97 Co 0.8 Fe 0.2 O 3-δThe Gd:Sr ratio x of the material was systematically varied in the range 0.1≤x≤0.9. Compared with the control example of Example 3, the two A-site cations carry different positive charges (Gd 3+ and Sr 2+ ), which results in better phase stability at high Gd contents: the materials with x < 0.2 have SF values ​​below 2.8 and are therefore expected to be phase stable under conditions relevant to industrial alkaline electrolysis. The materials with 0.2 ≤ x ≤ 1 in Table 5 are not phase stable.

[0068] Table 5

[0069]

[0070] Example 6

[0071] Table 6 lists some (La 0.6 A' 0.4 ) 0.99 Co 0.8 Fe 0.2 O 3-δ Related material properties and SF values ​​of the family of ceramic materials. Ca 2+ The ion radius of the Sanon ion at a coordination number of 12 is Sr 2+ The ionic radius at a coordination number of 9 is Ba 2+ The ionic radius at a coordination number of 12 is And Ce 3+ The ionic radius at a coordination number of 12 is In Table 6, the A-position cation A' is in (La 0.6 A' 0.4 ) 0.99 Co 0.8 Fe 0.2 O3 is systematically changed, A' is selected from Sr 2 + , Ca 2+ , Ba 2+ and Ce 3+ The SF values ​​of all materials in Table 6 are within the range of 1.67≤SF≤2.8, but the SF value of no material is within the range of 1.9≤SF≤2.6.

[0072] Table 6

[0073]

[0074] Example 7

[0075] Table 7 lists some (La 0.9 Sr 0.1 ) 0.97 BO 3-δThe relevant material properties and SF values ​​of the ceramic materials of the family. In Table 7, the B-site cation B' in (La 0.9 Sr 0.1 ) 0.97 BO 3-δ is systematically varied, and B' is selected from Mn, Ni, Fe, Co, Ti, and Cr. The average oxidation state of Mn, Ni, Fe, Co, and Cr ions is assumed to be 3.1. The exception is Ti, which is 4+ (6 coordination) exists, and its ionic radius is We obtain δ = -0.455. 3+ 、Co 4+ , Fe 3+ , Fe 4+ , Mn 3+ , Mn 4+ 、Ni 3+ 、Ni 4+ Cr 3+ and Cr 4+ The ionic radii of (both are 6-coordinated) are and The SF values ​​of all materials in Table 7 are in the range of 1.67≤SF≤2.8.

[0076] Table 7

[0077]

[0078] Example 8

[0079] Table 8 lists some (La 0.9 Sr 0.1 ) y BO 3±δ The relevant material properties and SF values ​​of the ceramic materials of the family. In Table 8, when 0.65≤y≤0.95 is determined, the B-site cation B' in (La 0.9 Sr 0.1 )yBO 3±δ is systematically varied, and B' is selected from Mn, Ni, Fe, Co, Ti, and Cr. The average charge of Mn, Ni, Fe, Co, and Cr ions is assumed to be 3.1, while Ti is set to Ti 4+ Comparing the SF values ​​in Table 8 with those in Table 7, it is clear that by reducing the A-site occupancy of the ceramic material, the SF value can be systematically increased, that is, by changing y, the activity and phase stability of the material can be adjusted. Some materials, such as (La 0.9 Sr 0.1 ) 0.90 TiO 3.31 , (La 0.9 Sr 0.1 )0.8 TiO 3.16 , (La 0.9 Sr 0.1 ) 0.65 TiO 2.94 and(La 0.9 Sr 0.1 ) 0.90 CrO 2.86 becomes too unstable (SF>2.8), while other materials remain relatively stable (1.67≤SF≤2.8).

[0080] Table 8

[0081]

[0082] Example 9

[0083] Table 9 lists the relevant material properties and SF values ​​of some ceramic materials of the lanthanum nickelate-ferrite family. 0.6 Fe 0.4 The SF value of O3 is 1.63, while the La 0.95 Ni 0.6 Fe 0.4 O 2.925 The SF value is 2.10. 0.90 Ni 0.6 Fe 0.4 O 2.85 The SF value of LaNi is 2.55. The SF values ​​of the materials with y≤0.85 in Table 9 are all over 2.8. 0.6 Fe 0.4 O3 is phase stable when exposed to 6M KOH at 80°C, while the materials with y≤0.85 in Table 9 are not phase stable. 0.5 Ni 0.6 Fe 0.4 O 2.25 , ceramic materials do not form perovskite structures, and multiphase and multicomponent materials exist even before exposure to industrial alkaline electrolysis conditions. In contrast, when y = 1, LaNi 0.6 Fe 0.4 O3 is not sufficiently active in the oxygen evolution reaction due to its very low SF value.

[0084] Table 9

[0085]

[0086]

[0087] Example 10

[0088] La 0.95CoO 2.925 , Pr 0.95 CoO 2.925 , Gd 0.95 CoO 2.925 , (La 0.9 Sr 0.1 ) 0.95 CoO 2.878 ,La 0.95 NiO 2.925 、LaFeO 2.925 ,La 0.95 Ni 0.6 Co 0.4 O 2.925 and La 0.95 Ni 0.6 Fe 0.4 O 2.925 The obtained materials were calcined at 800 °C for 3 h to obtain oxidation catalytic materials with perovskite structure, which were verified by X-ray diffraction measurements. The material properties and SF values ​​are summarized in Table 10.

[0089] Table 10

[0090]

[0091] The calcined materials were electrochemically treated in a rotating disk electrode (RDE) setup. To this end, each perovskite material was mixed with Nafion solution, isopropanol, and ultrapure water to make a slurry, which was then heated to a loading of 0.2 mg / cm 2 Coated on a glassy carbon electrode. The electrode was subjected to a three-electrode test in argon-saturated 0.1 M KOH. The oxygen evolution reaction (OER) kinetics were evaluated by applying a linearly varying voltage and measuring the corresponding current. The voltage potential was increased from 1.3 V to 1.9 V and then returned to 1.3 V relative to the standard of the reversible hydrogen electrode (RHE). The electrode was rotated at 1500 rpm and the measurement was performed at room temperature.

[0092] In addition, the materials were treated with strong bases to evaluate phase stability. Each material was treated with 6M KOH at 80°C for 100-120 hours. After treatment, the materials were thoroughly rinsed with distilled water, dried, and their crystal structures were studied using X-ray diffraction (XRD).

[0093] Specifically, the calcined Gd 0.95 CoO 2.925The material is mainly composed of perovskite materials, with the main XRD peaks at 2θ angles of 33.86°, 34.36° and 33.20° (in descending order of intensity). The material is highly active electrochemically: up to 10mA / cm 2 The voltage required for the OER current was 1.67 V. Due to its high stability factor (SF>2.8), the material was not phase stable after 6MKOH treatment. The main XRD peak changes were at 28.19°, 50.70°, 41.25°, and 29.52° 2θ angles, indicating that the original perovskite material had decomposed. The activity of the KOH-treated material in RDE measurements was significantly reduced (to 10 mA / cm 2 The required voltage is 1.73V). Gd 0.95 CoO 2.925 is an example of a material that is initially very active electrochemically but lacks phase stability under industrially relevant alkaline electrolysis conditions.

[0094] After calcination, La 0.95 Ni 0.6 Fe 0.4 O 2.925 The material is mainly composed of perovskite materials, with the main XRD peaks at 2θ angles of 32.56°, 32.84° and 46.94° (in descending order of intensity). The material is electrochemically active: up to 10mA / cm 2 The voltage required for the OER current was 1.66 V. Based on its SF value (1.67≤SF≤2.8), the material showed phase stability after 6 M KOH treatment. The main XRD peaks did not change, which were 32.60°, 32.80° and 46.98° at 2θ angles (in decreasing order of intensity), indicating that the original perovskite material remained stable under this treatment condition. The activity of the KOH-treated material in RDE measurements was slightly reduced, but still within an acceptable range (reaching 10 mA / cm 2 The required voltage is 1.72V). 0.95 Ni 0.6 Fe 0.4 O 2.925 is an example material that exhibits a good balance between good electrochemical activity and good phase stability under industrially relevant alkaline electrolysis conditions.

[0095] The calcined LaFeO3 material is mainly composed of perovskite material, with the main XRD peaks at 2θ angles of 33.16°, 57.40° and 46.16° (in decreasing order of intensity). The material is highly electrochemically inactive: when the voltage is increased to 1.9V, the current density is only 3.5mA / cm at 1.9V. 2 , failed to reach 10mA / cm2 The OER current was 2.3 %. Based on its low SF value (SF < 1.67), the material showed phase stability after 6 M KOH treatment. The main XRD peaks did not change, indicating that the original perovskite material was decomposed. LaFeO3 is an example material that is highly stable under industrially relevant alkaline electrolysis conditions but is not sufficiently active for OER.

[0096] The following steps can be followed to design an electrode suitable for oxygen evolution reaction in alkaline water electrolysis:

[0097] Step 1: Select the formula that satisfies [(A x )A' (1-x) ] y B z B' (1-z) O 3-δ Ceramic materials such as LaNi 0.6 Fe 0.4 O3,

[0098] Step 2: Use the SF calculation formula to estimate the SF value based on the ionic radius, oxidation state, A-site fraction (y), oxygen nonstoichiometry (δ), and A-site and B-site doping levels (x and z, respectively). For example, LaNi 0.6 Fe 0.4 The SF value of O3 is 1.63.

[0099] Step 3: If SF is within a suitable range (1.67≤SF≤2.8), the material can be synthesized using the method of Example 1 (but not limited to), and the ceramic material can be selected for further testing, for example, exposing the material to 6M KOH at 80 degrees Celsius for 100 hours to verify phase stability. For example, since SF<1.67, LaNi 0.6 Fe 0.4 O3 will not be selected for further testing.

[0100] Step 4: If SF is out of the appropriate range, adjust the y value to be in the range of 0.5 to 0.99, preferably in the range of 0.6 to 0.98 to change the SF value. For example, by changing the y value from 1.0 to 0.95 (from LaNi 0.6 Fe 0.4 O3 to La 0.95 Ni 0.6 Fe 0.4 O 2.925 ), the SF value can be increased to 2.1, thus satisfying the condition: 1.67≤SF≤2.8.

[0101] Step 5: As an alternative to step 4, the SF value can be changed by changing the value of x and / or z. For example, by changing the value of z from 0.6 to 0.1 (from LaNi0.6 Fe 0.4 O3 changed to LaNi 0.1 Fe 0.9 O3), the SF value can be increased from 1.63 to 1.65.

[0102] Step 6: As an alternative to step 4 or 5, the SF value can be changed by changing the elemental composition of the ceramic material. For example, by replacing Fe with Co, that is, changing the composition of the material from LaNi 0.6 Fe 0.4 O3 changed to LaNi 0.6 Co 0.4 O3, can increase the SF value from 1.63 to 1.64.

[0103] Step 7: Advantageously combine steps 4, 5 and 6. For example, by reducing y from 1 to 0.95, i.e., from LaNi 0.6 Co 0.4 O3 to La 0.95 Ni 0.6 Co 0.4 O 2.85 , the SF value can be increased from 1.64 to 2.04, thus satisfying the condition of 1.67≤SF≤2.8.

Claims

1. An electrode suitable for water electrolysis oxygen reaction under alkaline conditions, characterized in that: The electrode comprises a ceramic material satisfying formula (I): [(A x )A’ (1-x) ] y B z B’ (1-z) O 3-δ (I) wherein A and A' are each a rare earth metal or an alkaline earth metal, x is in the range of 0 to 1, y is the A site occupancy in the range of 0.5 to 0.99, B and B' are each a transition metal, z is in the range of 0 to 1, O is oxygen, and δ is the oxygen non-stoichiometric ratio in the range of -1 to 1; and The stability factor (SF) of the ceramic material satisfies formula (II): Among them, r O Oxygen ions (O 2- )'s Shannon ionic radius, r B,av is the weighted average Shannon ionic radius of B and B', satisfying formula (III): r B,Av =z·r B +(1-z)·r B′ (III) Among them, r B is the Shannon ionic radius of B, r B' is the ionic radius of B', n A,Av is the weighted average oxidation state of A and A', satisfying formula (IV): Among them, n A is the oxidation state of A, n A' is the oxidation state of A', r A,av is the weighted average ionic radius of A and A', satisfying formula (V): Among them, r A is the Shannon ionic radius of A, r A' is the ionic radius of A', The characteristics of the ceramic material satisfy the formula: 1.67≤SF≤2.

8.

2. The electrode according to claim 1, characterized in that The electrode further comprises a second material, which is metallic nickel, a metal alloy of iron and nickel, or hydroxides of nickel and iron.

3. The electrode according to claim 2, characterized in that The ceramic material satisfying formula (I) is uniformly dispersed on the surface of the second material.

4. The electrode according to claim 2 or 3, characterized in that Particles of the ceramic material are fixed and partially encapsulated in the second material.

5. An electrode according to any one of the preceding claims, characterized in that A is an element from the following list of elements: La, Ce, Gd, Pr, Ba; A' is an element from the following list of elements: Sr, Ca, Ba, Ce; and B or B' are each an element from the following list of elements: Mn, Ni, Fe, Co, Ti, Cr.

6. An electrode according to any preceding claim, characterized in that y is in the range of 0.6 to 0.98, preferably in the range of 0.75 to 0.

98.

7. An electrode according to any one of the preceding claims, characterized in that The average particle size of the ceramic material satisfying formula (I) is between 10 nanometers and 300 nanometers, preferably between 20 nanometers and 200 nanometers.

8. An electrode according to any preceding claim, characterized in that The ceramic material satisfying formula (I) has a perovskite crystal structure.

9. An electrode according to any preceding claim, characterized in that When the oxygen evolution reaction was carried out at a current density of 1 mA / cm2 using a rotating disk electrode at a speed of 1500 rpm in 20-35 wt% KOH at a temperature of 75 to 85 degrees Celsius, 2 When the overpotential of the electrode to the oxygen evolution reaction is less than or equal to 400 millivolts.

10. An electrode according to any preceding claim, characterized in that The ceramic material satisfying formula (I) has a phase stability of 100 hours in 6M KOH at 80 degrees Celsius.

11. An electrode according to any preceding claim, characterized in that 1.9≤SF≤2.

6.

12. An alkaline electrolysis stack comprising at least one electrode as claimed in any preceding claim.

13. A method for electrolyzing water under alkaline conditions using the alkaline electrolysis stack according to claim 12.

Citation Information

Patent Citations

  • Cathode material of solid oxide electrolysis cell and preparation method thereof

    CN106498435A

  • Layered perovskite-type oxide, preparation method and use thereof in the oxygen evolution reaction electrocatalyst

    CN108579751A

  • A A-site vacancy type perovskite oxygen catalyst, a preparation method and application thereof

    CN109088077A

  • Positive electrode, positive electrode for water electrolysis, electrolysis cell, and method for producing hydrogen

    CN110199055A

  • Electrochemical methods and systems using catalytic materials

    WO2013012965A1